2019
DOI: 10.20409/berj.2019.177
|View full text |Cite
|
Sign up to set email alerts
|

Bireysel Emeklilik Şirketlerinin Entropi Ağırlıklı ARAS ve COPRAS Yöntemleri ile Karşılaştırmalı Performans Değerlendirmesi

Abstract: Bireysel emeklilik sistemi, bireylerin emeklilik dönemlerinde ek bir kazanç elde etmelerini sağlayarak bireylerin emeklilik dönemlerini refah içinde geçirmelerine destek olmaktadır. Bireysel emeklilik sistemi uygulandığı ülkelerde, hem sosyal güvenlik sisteminin tamamlayıcısı olarak hem de uzun vadeli yatırım fonları olarak ekonomiye katkı sağlamaktadır. Sistemde toplanan fonlar ise emeklilik branşında faaliyet göstermek üzere özel portföy yönetim şirketleri tarafından yönetilmektedir. Bu çalışmanın amacı ise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Then, the MARCOS procedure is used to rank private pension and life insurance companies. As far as we know, unlike previous studies (Genç et al, 2015;Özbek, 2015;Ege et al, 2016;Şahin and Başarir, 2019;Noyan et al, 2019;Bayrakci and Aksoy, 2019;Acer et al, 2020;Uçar and Şahin, 2020), the financial performance analysis of life and pension companies is carried out within the framework of the SD-MARCOS model for the first time in this study. In other words, in spite of the fact that there are many studies in the previous literature focusing on financial performance analysis of life and pension companies in Turkey, no study using the SD-MARCOS performance evaluation model is found in the previous literature.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the MARCOS procedure is used to rank private pension and life insurance companies. As far as we know, unlike previous studies (Genç et al, 2015;Özbek, 2015;Ege et al, 2016;Şahin and Başarir, 2019;Noyan et al, 2019;Bayrakci and Aksoy, 2019;Acer et al, 2020;Uçar and Şahin, 2020), the financial performance analysis of life and pension companies is carried out within the framework of the SD-MARCOS model for the first time in this study. In other words, in spite of the fact that there are many studies in the previous literature focusing on financial performance analysis of life and pension companies in Turkey, no study using the SD-MARCOS performance evaluation model is found in the previous literature.…”
Section: Discussionmentioning
confidence: 99%